Prevalence and determinants of restrictive lung disorder among quarry workers at the Umuoghara quarry site, Ebonyi State, Nigeria: a cross-sectional study - Ngozika Substance Ike-Samuel; Osaeloka C. Ekwueme; Susan Chioma Udeh (BMC Pulmonary Medicine)
Abstract Introduction Respiratory disorders pose a serious health risk for quarry workers exposed to dust, as they are a leading source of morbidity and mortality globally, often resulting in irreversible lung conditions. This study assessed the prevalence and determinants of restrictive disorder among quarry workers in Umuoghara quarry site, Ebonyi State. Methods This study was done on quarry workers at the Umuoghara quarry site, Ebonyi State. An analytical cross-sectional study design was adopted. Data was collected using a pre-tested semi-structured questionnaire among 300 quarry workers selected by simple random sampling method. Lung function test was performed using a spirometer- spirovit SPI schiller and data was analyzed with the use of IBM SPSS version 23.0. Pearson’s chi-square test was used to find associations between variables. Binary logistic regression (multivariate analysis) was used to find the determinants of restrictive lung disorder at p < 0.05. Results The prevalence of restrictive disorder was 14.3%. Working for more than 5 years (AOR = 2.880 at 95% CI = 1.234–6.720), Working for more than 10 years (AOR = 9.645 at 95% CI = 2.601–35.766), smoking (AOR = 3.558 at 95% CI = 1.631–7.762) and non-use of protective measures (AOR = 0.114; 95% CI = 0.050–0.262) were the determinants of restrictive lung disorder in quarry workers. Conclusion There is an increased risk of developing respiratory problems among quarry workers exposed to quarry dust. It is recommended that employees receive thorough education on the dangers of this exposure, and that employers be mandated to provide protective equipment and strictly enforce its use among workers.